Aplikasi Suplementasi Cairan Silase Rumput Rawa sebagai Feed Additive untuk Ternak Itik di Desa Kota Daro II: Application of Swamp Grass Silage Liquid as a Feed Additive for Ducks in Kota Daro II Village - Fitra Yosi; Asep Indra Munawar Ali; Mirza Lena; Mirza Antoni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Kota Daro II Village is located in Rantau Panjang Subdistrict, Ogan Ilir Regency, South Sumatra Province. This community service activity aimed to provide education and training for farmers on using swamp grass silage liquid as a feed additive for ducks. The target partners were the “Harapan Maju I” farmer group, consisting of 20 farmers. The method used is Participatory Rural Appraisal, which encourages community participation. There were two stages: preparation and implementation. During the preparation stage, approaches were made to relevant parties, such as village officials, community leaders, and the head of the farmer group. During the implementation stage, field visits were conducted. During the visits, education and demonstrations/hands-on practice were carried out by farmers on the application of silage technology using swamp grass silage liquid as a source of feed additive. The results of activities show that the enthusiasm of the community and duck farmers in Kota Daro II Village, Rantau Panjang Subdistrict, for the training activity is very high. This is due to farmers' limited knowledge of feed processing technology, particularly the use of feed additives in the form of swamp grass silage liquid as a source of probiotics and phytobiotics beneficial to the health and productivity of ducks.